Costs and cost-effectiveness of palliative care in residential aged care homes: a scoping review. - Yang, Xueqing; Liu, Fengyi; MacAndrew, Margaret; White, Nicole; Carter, Hannah Elizabeth (Age & Ageing, 2026)
Background Palliative care is increasingly recognised as a core component of healthcare delivery in residential aged care (RAC) homes, yet its economic implications remain unclear. Understanding costs and cost-effectiveness is essential for guiding resource allocation decisions in these settings. Objective To map the evidence on the costs and cost-effectiveness of palliative care delivered in RAC homes, and to identify gaps in the evidence base. Methods A scoping review was conducted in accordance with Joanna Briggs Institute guidelines and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews checklist. Searches were conducted in the PubMed, SCOPUS, Embase, CINAHL and CENTRAL databases. Studies reporting on quantitative economic outcomes of palliative care in RAC settings were included. Findings were summarised using narrative synthesis. Results Of the 3182 items identified, 15 studies were included. Three categories of economic outcomes were identified: care delivery costs (n  = 3), healthcare system costs (n  = 10) and cost-effectiveness outcomes (n  = 2). Studies examining care delivery costs reported additional costs associated with palliative care. Among studies assessing healthcare system costs, six reported reduced costs, one reported increased costs and three reported mixed findings varying by time horizon and care continuity. Two full economic evaluations reported favourable cost-effectiveness findings compared with usual care, although the statistical significance of findings varied. Conclusion Economic evidence on palliative care in RAC remains limited and methodologically heterogeneous, constraining robust conclusions regarding its economic value. Future research should prioritise rigorous economic evaluations that comprehensively capture healthcare and social care costs while incorporating patient-centred outcomes to better assess the value of palliative care in RAC homes.